(untitled) (Journal of Dhaka Medical College, 2021)
Pre -eclampsia is a disorder of 2nd half of pregnancy, which is characterized by a combination of hypertension, proteinuria and edema, secondary to decreased placental perfusion. Clinical studies suggest that antioxidant vitamins, such as Vit C and Vit. E can stabilize reactive free radicals, which are produced due to placental hypo perfusion, thereby preventing the development of pre-eclampsia. Pre-eclampsia remain a major cause of infant and maternal mortality and morbidity. In developing countries, pre-eclampsia causes an estimated 50,000 maternal deaths per year. Only a small number of studies have however, been conducted in Bangladesh. Objective: To compare the serum levels of antioxidants in selected pre-eclamptic and normotensive pregnant women. Methods: 220 pregnant women were selected with inclusion and exclusion criteria from 3 different medical colleges and divided into 2 groups – A study group, consisting of 110 pre-eclamptic women and a control group consisting of 110 normotensive pregnant women. Dietary information was collected by 7 days food frequency questionnaire and food score was determined. Anthropometric and biochemical tests were performed. Biochemical analysis such as serum vitamin C levels were measured by spectrophotometric method, and serum vitamin E levels were measured by HPLC (High Performance Liquid Chromatography) method. Results: The mean serum levels of Vit. C and Vit E were found to be significantly lower in the study group, compared to the control group. Anthropometric study revealed that the babies born to pre-eclamptic mothers had lower birth weight than those born to normotensive mothers. Conclusion: Therefore, low antioxidant levels do play a key role in the development of preeclampsia in pregnant women. J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 53-58